SYSTEM FOR MONITORING CONSUMABLE WATER QUALITY BASED ON INTERNET OF THINGS - Muhammad Sapriadi; Muhammad Fikry; Ar Razi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Access to clean and consumable water is a critical factor for public health, but not all communities have the tools to monitor water quality in real-time. To address this issue, this study proposes the development and implementation of an Internet of Things (IoT)-based water quality monitoring system. The system is designed to measure key water quality parameters such as pH, Total Dissolved Solids (TDS), turbidity, and temperature, using an ESP32 microcontroller. This microcontroller is connected to a variety of sensors and integrated with the Blynk application, which allows users to monitor the data through their mobile devices. The system also incorporates a rule-based decision-making method that classifies the water as consumable or not, based on predetermined standards. The IoT-based system ensures smooth data transmission to the Blynk app, and the decision-making process is accurate and reliable. This system provides a practical and efficient solution for real-time water quality monitoring, especially for communities lacking advanced water quality monitoring tools. It enables users to assess water quality remotely, offering a significant improvement in public health monitoring and management.